Studi Teknis Dan Ekonomis Dimensi Konstruksi Kapal Kayu Berdasarkan BKI - Aditya, Bagus Kusuma; Supomo, Heri; Ma'ruf, Buana (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2020)
Wooden ships are one of the non-steel ships that are widely available in Indonesian waters, which are built using conventional methods. In this study, a survey was conducted to determine the dimensions of the construction elements on the ship's kasko from the keel to the main deck, the price of wood materials and the construction process using interview and observation methods. Existing ship data is analyzed according to the 1996 BKI Rule on wooden ships to determine the level of comparison for each element of ship construction. Existing ship construction data based on regulatory analysis is modeled to get the optimum reductions of construction dimensions. Based on the results of the technical and economic analysis of the three vessels, it is known that the two existing ships have heavier construction than the calculation according to the BKI Rules. This is influenced by differences in ivory spacing, deck beam distance, outer shell thickness and deck thickness. The size of the construction dimensions is proportional to its economic value. Therefore, to determine the optimum level of reduction in construction dimensions, structural modeling is used. In the modeling that is done, it is found that the value of the reduction in construction dimensions is 10%, 20% and 30%. This reduction was carried out because the magnitude of the stress of the three ships according to the BKI Rules was still far below the limit allowed according to BKI 12,75 N/mm2. According to the results, the recommendation for the reduction in construction dimensions is up to 20%. The Â 30% reductions were not recommended because the stress value is over than the stress limit. The allowable stress is 12,75 N/mm2. Based on the data, it can be conclude that the economic value also can be reduced up to 20%.